Peculiarities of relationships between plasma levels of nitrogenous metabolites and EEG & HRV parameters in patients with postradiation encephalopaty - Bombushkar, Igor; Gozhenko, Anatoliy; Korda, Mykhaylo; Żukow, Xawery; Popovych, Igor (Journal of Education, Health and Sport, 2022)
Background. Recently we shown that nitrogenous plasma metabolites (uric acid, bilirubin, urea and creatinine), even in the absence of uremia, are able to influence the state of the anxiety, autonomic and central nervous and endocrine systems, apparently through aryl hydrocarbon and adenosine receptors of neurons and endocrine cells and/or directly. Sexual dimorphism in the neurotropic effects of uric acid in neurologically healthy patients was also revealed. The purpose of this study is to compare nitrogenous-neural relationships in neurologically healthy men and those with post-radiation encephalopathy (PREP). Materials and Methods. The object of observation were neurologically healthy 31 men (24÷69 y) and 19 patients (26÷61 y) with PREP. The relationships between plasma levels of nitrogenous metabolites, on the one hand, and EEG and HRV parameters, on the other, were analyzed. Results. By constructing regression models with stepwise elimination it was found that the multiple correlation coefficient (R±µ) of creatinine with neural parameters in patients with PREP significantly exceeded that of control patients (0,762±0,069 vs 0,409±0,107; t=2,62; p=0,011). With regard to urea, the differences are insignificant (0,801±0,059 vs 0,694±0,066; t=1,17; p>0,2), and with regard to bilirubin (0,548±0,115 vs 0,402±0,107; t=0,94) and uric acid (0,496±0,124 vs 0,549±0,089; t=0,32), there are practically no differences. Conclusion. Post-radiation encephalopathy is accompanied not only by deviations from the norm of a number of EEG and HRV parameters, but also by their increased sensitivity to creatinine and, to a lesser extent, urea, but not to bilirubin and uric acid.